Concentration and competition in the U.S. fertilizer industry - Bart L. Fischer; Joe L. Outlaw; Henry L. Bryant; J. Marc Raulston; George M. Knapek (Texas A&M University, The Agricultural & Food Policy Center (AFPC), 2024)
Between September 2021 and April 2022, anhydrous ammonia prices in the United States more than doubled, topping out at a record-high 1,300/ton. At the time, Senator John Boozman, Ranking Member of the Senate Committee on Agriculture, Nutrition, and Forestry, asked the Agricultural & Food Policy Center (AFPC) at Texas A&M University to analyze the impact of significant increases in input costs - particularly fertilizer costs - on farms and ranches across the United States.1 While cost has since abated somewhat for most inputs, the spike in prices in 2022 renewed concerns about competition (or the lack thereof) in the fertilizer industry. As a result, Senators John Thune (R-SD) and Amy Klobuchar (D-MN) asked AFPC to provide an updated analysis of trends in the correlation between fertilizer costs and commodity prices, an overview of fertilizer price transparency, and the outlook for domestic fertilizer production capacity. The Senators also requested updated information about concentration levels in the fertilizer industry and policy considerations that could increase competition. This report was prepared in response to their request.
Keywords: 330; Düngemittelindustrie; Unternehmenskonzentration; Branchenentwicklung; USA